2020
DOI: 10.26434/chemrxiv.12570551.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Identification of Potential Allosteric Inhibitors of the SARS-CoV-2 Helicase

Abstract: <p>The COVID-19 pandemic ravages the globe causing unprecedented health and economic challenges. As the world prospects for a cure, scientists are looking critically at strategic protein targets within the SARS-CoV-2 that have therapeutic significance. One of such targets is the Helicase which is an enzyme that affects all aspects of SARS-CoV-2 RNA metabolism. The aim of this study is to identify small molecules from natural products that have strong binding affinity with and inhibitory activity against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In this study, Glycyrrhizin binds to an allosteric site near the catalytic cleft, while Glycyrrhetinic acid interacts with residues in stalk and 1B domain. Triphenyamine and Darunavir have been reported to bind the same active site [ 102 ]. Rutin, xanthones, and many other polyphenols have been reported to be ATPase inhibitors [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Glycyrrhizin binds to an allosteric site near the catalytic cleft, while Glycyrrhetinic acid interacts with residues in stalk and 1B domain. Triphenyamine and Darunavir have been reported to bind the same active site [ 102 ]. Rutin, xanthones, and many other polyphenols have been reported to be ATPase inhibitors [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PCA is used to statistically evaluate the various structural conformations of a protein generated during trajectories [69]. This study found that the BrucMetRS -Isopteropodin complex has the greatest global (total and average) motions of any holo structures, closely followed by the BrMelMetRS-OOU complex.…”
Section: Analyses Of Time-resolved Trajectoriesmentioning
confidence: 99%